The course of pregnancy and delivery in a patient with acute myeloid leukemia. A case report - Krekora, Michał; Biesiada, Lidia; Kędzierska, Anna; Pluta, Agnieszka; Krajewski, Piotr; Robak, Tadeusz; Krasomski, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2011)
It is estimated that approximately 1/1000 pregnancies is complicated by the occurrence of cancer of which the cervical cancer accounts for the majority of cases. As leukemia affects approximately 1/100,000 pregnant women, currently there are few reports on treatment during gestation and further consequences of any therapy for children born from such pregnancies. Treatment of leukemia during pregnancy is much more difficult due to the fact that the therapy has to be chosen individually depending on the advancement of pregnancy as well as the health condition of both the mother and the child. Despite the controversy of applying chemotherapy in pregnant women, this procedure seems to be presently the best solution as the adverse effects of treatment decrease with advancement of pregnancy.